TECHNOLOGICALLY OR ECONOMICALLY OPTIMAL OZONATION OF BULK LIVE FEED - Dubrovin, A. (Енергетика і автоматика, 2016)
A device for ozonation moving loose forages are designed. Production is carried out in automatic mode according to technological or economic criteria.